Determination of glutamate in Food Samples by heterogeneous Membrane with chitosan as ionophore - Illyas Md Isa (Tanjong Malim, 2009)
Determination of glutamate in Food Samples by heterogeneous Membrane with chitosan as ionophore by Illyas Md Isa